Promoting pharmacy with purpose: faculty of pharmacy’s strong presence at UiTM ESKU 2025 - Ibrahim, Nurul Alyaa (Faculty of Pharmacy, 2025)
On 17th and 18th May 2025, the Faculty of Pharmacy, UiTM Cawangan Pulau Pinang (Bertam Campus) successfully participated in the Ekspo Selangkah ke UiTM (ESKU) 2025. This annual event was held at Tun Abdul Razak Library (PTAR), UiTM Cawangan Pulau Pinang (Permatang Pauh Campus), from 9.00 am to 5.30 pm on both days. The main objective of ESKU is to provide an informative and engaging platform for school leavers and the public about various academic programs and opportunities offered by UiTM, specifically in UiTM Pulau Pinang.